Role of neuropilin-2 in the immune system. (October 2017) - Schellenburg, S.; Schulz, A.; Poitz, D.M.; Muders, M.H.
Highlights: Neuropilin-2 is important for the maturation of macrophages. Neuropilin-2 plays an essential role in the activation of dendritic cells. Neuropilin-2 helps in the maturation and activation process of T-lymphocytes. Posttranslational polysialylation regulates the function of neuropilin-2 in the immune system. Abstract: Neuropilins (NRPs) are single transmembrane receptors with short cytoplasmic tails and are dependent on receptors like VEGF receptors or Plexins for signal transduction. NRPs are known to be important in angiogenesis, lymphangiogenesis, and axon guidance. The Neuropilin-family consists of two members, Neuropilin-1 (NRP1) and Neuropilin-2 (NRP2). They are up to 44 % homologous and conserved in all vertebrates. High levels of NRP2 are found on immune cells. Current research is very limited regarding the functions of NRP2 on these cells. Recent evidence suggests that NRP2 is important for migration, antigen presentation, phagocytosis and cell–cell contact within the immune system. Additionally, posttranslational NRP2 modifications like polysialylation are crucial for the function of some immune cells. This review is an overview about expression and functions of NRP2 in the immune system.